Syrian Arab Republic : 2005 Article IV Consultation; Staff Report; and Public Information Notice on the Executive Board Discussion. (IMF Staff Country Reports; Country Report ;, 2005)
The Syrian Arab Republic's 2005 Article IV Consultation reports that progress had been made on structural reforms, including a simplification of the exchange rate system, and the adoption of a new income tax law. Rising international oil prices starting in mid-1999 helped maintain financial stability in the face of declining oil production. Government policies and IMF advice since the early 2000s have focused primarily on structural reforms to boost growth and also on strengthening the medium-term budgetary outlook, given the prospective decline in oil revenues.